Inferior alveolar nerve preservation for hemimandibulectomy and bridging plate reconstruction in monostotic fibrous dysplasia case - Agus Widodo; Muhammad M. Rahmat; Prihartiningsih Prihartiningsih; Cahya Y. Hasan (Journal of Dentomaxillofacial Science, 2020)
Objective: This paper aimed to report the inferior alveolar nerve preservation in cases of monostotic fibrous dysplasia performed by hemimandibulectomy.Methods: A 11-year-old boy was referred to Dr. Sardjito General Hospital with the complaint of having a lump at the lower back of the left jaw. Past medical history revealed that the patient fell and knocked a stone on the left jaw, at 8 years old. The patient was biopsied and diagnosed with monostotic fibrous dysplasia. From the result of the investigations conducted, the lesion had involved the left coronoid and condyle processes.Results: The treatment performed for this case were hemimandibulectomy and reconstruction with installation of bridging plates to remove lesions, restore masticatory function and facial esthetics. Postoperative evaluation showed shape and jaw function was restored with no complaint of paresthesia.Conclusion: Inferior alveolar nerve preservation was performed to minimize the symptoms of paresthesia as the patient was still young, the lesion was benign and had a low recurrence rate if it was taken cleanly.